圆[img=211x26]1802db2e179908c.png[/img]的圆心为(-1,2),则圆的半径是( )
A: 6
B: 9
C: 3
D: 2
A: 6
B: 9
C: 3
D: 2
C
举一反三
- 圆[img=211x26]180305a187eb552.png[/img]的圆心为(-1,2),则圆的半径是( ) A: 6 B: 9 C: 3 D: 2
- 圆[img=211x26]18037043b2ad0a3.png[/img]的圆心为(-1,2),则圆的半径是( ) A: 6 B: 9 C: 3 D: 2
- 圆[img=211x26]1803ccf54eed760.png[/img]的圆心为(-1,2),则圆的半径是( ) A: 6 B: 9 C: 3 D: 2
- 圆[img=211x26]1802e717ed63669.png[/img]的圆心为(-1,2),则圆的半径是( ) A: 6 B: 9 C: 3 D: 2
- 圆[img=211x26]180366a62e2dff4.png[/img]的圆心为(-1,2),则圆的半径是( ) A: 6 B: 9 C: 3 D: 2
内容
- 0
圆[img=56x26]1802ec511a0c373.png[/img]+Dx+Ey-4=0的圆心为(-1,2),则圆的半径为() A: 6 B: 9 C: 3 D: 2
- 1
圆[img=56x26]1803ccf5be74189.png[/img]+Dx+Ey-4=0的圆心为(-1,2),则圆的半径为() A: 6 B: 9 C: 3 D: 2
- 2
圆[img=56x26]18038de8e0cd9d2.png[/img]+Dx+Ey-4=0的圆心为(-1,2),则圆的半径为() A: 6 B: 9 C: 3 D: 2
- 3
圆[img=56x26]1802e7afb41419d.png[/img]+Dx+Ey-4=0的圆心为(-1,2),则圆的半径为() A: 6 B: 9 C: 3 D: 2
- 4
圆[img=56x26]180366a51fb7e93.png[/img]+Dx+Ey-4=0的圆心为(-1,2),则圆的半径为() A: 6 B: 9 C: 3 D: 2